The effect of motor experience on knee stability and inter-joint coordination when cutting at different angles - Pan, Zhengye; Liu, Lushuai; Ma, Yunchao (The knee, 2024)
Most studies on cutting have focused on the biomechanics of the knee and lower-limb muscle activation characteristics, with less consideration given to the influence of motor experience on control strategies at the joint level. This study aimed to investigate the differences in knee stability and inter-joint coordination between high- and low-level athletes when cutting at different angles. A Vicon motion capture system and a Kistler force table were used to obtain kinematic and ground reaction force data during cutting. Joint dynamic stiffness and vector coding were used to assess knee stability and inter-joint coordination. Uncontrolled manifold analysis was used to clarify whether there was synergy among lower-limb joints to maintain postural stability during cutting. During the load acceptance phase, skilled subjects had the smallest joint stiffness at 90° compared with novice subjects (P < 0.05). Compared with novice subjects, skilled subjects had smaller knee–hip ellipse areas at 90° and 135° (P < 0.05), but larger knee–ankle ellipse areas at 135° (P < 0.05). The synergy index in load acceptance was significantly higher (P < 0.05) for skilled subjects at 90° and 135°. Advanced subjects can adjust joint control strategies to adapt to the demands of large-angle cutting on the change of direction. Advanced subjects can reduce knee stability for greater flexibility during cutting compared with novice subjects. By increasing the degree of synergy among the lower-limb joints, advanced athletes can maintain high postural stability.